2016
DOI: 10.2174/1570162x14666160324124132
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Opioid Maintenance Therapies: Their Impact on Monocyte-Mediated HIV Neuropathogenesis

Abstract: Background-HIV-1 enters the CNS within two weeks after peripheral infection and results in chronic neuroinflammation that leads to HIV associated neurocognitive disorders (HAND) in more than 50% of infected people. HIV enters the CNS by transmigration of infected monocytes across the blood brain barrier. Intravenous drug abuse is a major risk factor for HIV-1 infection, and opioids have been shown to alter the progression and severity of HAND. Methadone and buprenorphine are opioid derivates that are used as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 140 publications
(196 reference statements)
0
10
0
Order By: Relevance
“…Opioids have been shown in some studies to augment HIV neuropathogensis and their effects are still present in the current ART era . One mechanism by which opioids may increase HIV neuropathogenesis is by modulating the functions of immune cells . This is supported by the fact that these cells, including monocytes, express opioid receptors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioids have been shown in some studies to augment HIV neuropathogensis and their effects are still present in the current ART era . One mechanism by which opioids may increase HIV neuropathogenesis is by modulating the functions of immune cells . This is supported by the fact that these cells, including monocytes, express opioid receptors .…”
Section: Discussionmentioning
confidence: 99%
“…Opioid abuse is important in the context of HIV infection and neuropathogenesis since some studies have shown that HIV infected people who use opioids have increased CNS disease compared to infected non-opioid abusers [3639]. The mechanisms by which opioids contribute to HIV neuropathogenesis are not fully understood, but regulation of immune cell functions is believed to be important [4042].…”
Section: Introductionmentioning
confidence: 99%
“…al. 2016 ). In S. pneumoniae -infected mice, morphine and/or Tat exposure significantly enhances immune cell trafficking into the brain via actions at TLR2 and TLR4 (Dutta and Roy 2015 ).…”
Section: Hiv Neuropathology In the Context Of Opioid Use Disorder – Cmentioning
confidence: 99%
“…In primary astrocytes, agonist-selective actions at MOR and KOR can be clearly demonstrated (Bohn et al 2000 ; Belcheva et al 2003 ; McLennan et al 2008 ; Hahn et al 2010 ), and we found that morphine, methadone, and buprenorphine differentially increase ROS and [Ca 2+ ] i alone or following Tat co-exposure (Fitting et al 2014b ). Morphine can enhance HIV-1-induced production of cytokines and specifically chemokines (El-Hage et al 2008a ; Dave 2012 ; El-Hage et al 2014 ), while other opioids including methadone, oxycodone, buprenorphine, and DAMGO can decrease inflammatory function and decrease monocyte migration (Boland et al 2014 ; Carvallo et al 2015 ; Jaureguiberry-Bravo et al 2016 ; Chilunda et al 2019 ).…”
Section: Questions Remaining – Future Directionsmentioning
confidence: 99%
“…OUD is important in the context of HIV infection, as several studies have reported that PLWH who use opioids are at a higher risk of developing neurological disorders compared to PLWH without OUD [15][16][17][18][19][20]. Opioids have been shown to upregulate the expression of CCR5 while downregulating the expression of its cognate β-chemokine production by acting through µ-opioid receptor in macrophages and microglia, thereby boosting the entry of R5 tropic viruses in these target cells [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%